Pelatihan Keterampilan Berkomunikasi Berbasis Merdeka Belajar Bagi Pendidik Paud Aisyiyah Bustanul Athfal 14 Surabaya Untuk Mengembangkan Kemampuan Bahasa Anak - Ahmad Fachrurrazi; Made Ayu Anggreni (BADAN PENERBIT STIEPARI PRESS, 2023)
Learning at the level of any educational unit will really need communication, because communication plays an important role in the learning process. Without effective communication the learning process will not be optimal. On this basis it is very important for educators to master communication skills so that learning is carried out effectively and achieves the expected goals. Freedom to learn in early childhood education is specified as freedom to play, where students are facilitated with freedom to learn and play so that their growth and development can develop optimally. Language skills for early childhood is one aspect of development that is very important to develop. From this language ability students will be able to develop other abilities such as understanding concepts, interacting with others, developing imagination and creation and so on. These three pillars-communication skills, independent play, and language skills-are things that need special attention in order to improve the quality of early childhood education. In connection with these three pillars, the Early Childhood Education Teacher Education Study Program, Faculty of Pedagogy and Psychology, PGRI Adi Buana University, Surabaya carries out Community Service in the form of Freedom-Based Communication Skills Training, Free Learning to Play, to Develop Children's Language Skills in Aisyiyah Bustanul Athfal 14 Kindergarten, Surabaya, with the aim improve knowledge and communication skills for teachers to develop children's language skills based on independent learning to play independently.